Towards a global history of the Unidad Popular. (1st June 2021) - Harmer, Tanya
Abstract : Our understanding of the international and transnational history of Chile during the Unidad Popular (UP) government has expanded considerably since the early 2010s. But what has new research contributed to our understanding of events in Chile and Chile's significance in a global context? Examining the historiographical advances and questions that have driven scholarship in recent years, this article argues that international and transnational studies that focus attention on Chile and Chileans can offer new perspectives on the rise and fall of the UP. Rather than reducing international histories to an account of a select group of foreigners acting on an empty Chilean stage, these approaches foreground local actors and processes, exploring the extent to which Chileans were shaped by a multiplicity of interactions, invitations and inspirations across borders. Localising the global in this way can help us understand the reasons many within Chile conceptualised their goals, projects and actions as they did. It challenges the idea of Chilean exceptionalism. It also undermines right-wing actors' claims to be acting solely within national frameworks by revealing their own entanglements in translational networks and intellectual imports. Suggesting that we have much still to learn, the article also highlights possible avenues for further research and reflects on the contemporary relevance of the global in Chilean political discourse today.